A randomized controlled trial examining a Tranquil sitting intervention compatible with Confucian values - Wen, Xiaochen; Zhou, Yaping; Li, Yinan; Lv, Yue; Han, Siyi; Zhao, Junshu (Frontiers in Psychology, 2023)
Introduction During the COVID-19 pandemic in China, the silent management (Lockdown) policy has caused severe sleep problems for university students. Long-term isolation may further deteriorate sleep quality, and it requires practical interventions. Today in mental and sleep health, interventions based on Buddhist, Taoist and Confucian ethics have been proven effective in reducing cognition and sleep disorders. However, such interventions also have limitations. They tend to focus on peace of mind or some technical means with the main direction of symptom improvement but neglect the mundane activities of daily life. Methods We conducted an innovative tranquil sitting intervention program based on the Chinese Confucian value of the “tranquility and reverence” method, integrating various intervention techniques traditionally recognized as effective for achieving more lasting mental health and sleep quality. This study aims to assess the effectiveness and feasibility of a tranquil sitting intervention in improving sleep problems in isolated university students. Using a randomized control trial (RCT), the participants in the intervention program (n = 35) practiced the tranquil sitting intervention program for ten weeks. They had their PSQI scores measured at the pre-experimental, post-test, and 1-month follow-up time points and compared to the control group (n = 35). Results The participants who received the tranquil sitting intervention had significantly better sleep quality than the control group, with moderate to large effect sizes in the middle and late stages. The instructor may challenge the intervention group at the beginning of the tranquil sitting technique. However, the improvement in sleep quality was significant after fully mastering the method. Discussion The intervention program in this study emphasized the importance of “tranquility” and showed the same sleep improvement as in other traditional interventions. In conclusion, this intervention is a feasible and promising new approach to improving sleep quality among youths.